A Descriptive study and analysis of the codeswitching patterns in GMA 7's Frontpage codeswitching as the preferred communicative style of Filipinos - Latosa, Augustus Ceasar D.; Magdalera, Mayen Aea F. (College of Arts and Letters, University of the Philippines Diliman, 2004)
This descriptive-analytical research is a study on the use of codeswitching as a communicative style on television news, specifically GMA-7's Frontpage. The specific objectives of this research are: 1) To describe how codeswitching is used in television news. 2) To determine how the content of the news program affects the process of codeswitching and what are the factors that necessitate codeswitching. 3) To establish how codeswitching reflects the Filipinos' preferred communicative style. 4) To determine how codeswitching as a communicative style on television news resolve the conflict of social relations, if there is any, in a multilingual society. The framework of this study is based on Media Discourse by Fairclough (1995), Code-switching and codemixing in multingual societies by Marasigan (1983), and Interlingual Discourse in Theory and Practice by de Beaugrande (1997). The primary data used in this research are five episodes of Frontpage, the primetime news program of GMA-7 - one of the biggest broadcasting networks in the Philippines. The aural components of the episodes were (tape) recorded and transcribed. The researchers found out that codeswitching is used on all segments of the news program and that it affects the formality of the program in different ways. Overall, codeswitching is used mainly to deal with Technical Subject, and the most prevalent form of codeswitching in the news program is Lexical Borrowing. The researchers came up with the following conclusions: 1) Codeswitching is used to negotiate the discussion of Technical Subject. 2) Content affects the instances when anchors and field reporters use codeswitching. And that codeswitching is necessary to keep the degree of relevance to the subject and to retain faithfulness to the original. 3) Codeswitching bridges the gap between the communicative styles of the educated and elite and the common folk. This research implies the codeswitching is a way of reconciling differences in audience types in order to make a news program able to cater to as many audience as possible. Recommendations on further studies are also provided in this research.